1986
DOI: 10.1002/lary.1986.96.11.1211
|View full text |Cite
|
Sign up to set email alerts
|

Homograft (Allograft) Tympanoplasty Update

Abstract: If homograft tympanoplasty is to be of value, specific instances in which homograft tympanic membrane, malleus, and incus (TMMI) provide significant hearing and anatomical advantages over standard techniques should be identified. This author has performed 305 homograft tympanoplasties limited to the reconstruction of the severely damaged middle ear. Indications include: previous failure with standard tympanoplasty techniques; high risk of anatomic or hearing failure with standard techniques (total perforation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 13 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…With allograft incus transposition in M-S+ defect, we got satisfactory result in 50% (2 cases). Bahadur et a1 [4] had a-b gap closure to 15 dB or less in 60% (6 cases) and Lesinski [5] had in 80% (47 cases). Intragroup comparison between autograft and allograft ossicles shows satisfactory results in 80% and 60% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…With allograft incus transposition in M-S+ defect, we got satisfactory result in 50% (2 cases). Bahadur et a1 [4] had a-b gap closure to 15 dB or less in 60% (6 cases) and Lesinski [5] had in 80% (47 cases). Intragroup comparison between autograft and allograft ossicles shows satisfactory results in 80% and 60% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the late 1960s, the development of tympano‐ossicular homograft procedures produced major progress in reconstructive surgery of the middle ear 1,2 . Numerous studies were published that demonstrated the outstanding results obtained with this new surgical approach 2‐10 . However, the spread of the human immunodeficiency virus (HIV) epidemic during the 1980s produced a major setback in the use of homografts.…”
Section: Introductionmentioning
confidence: 99%